The Effect of an Augmented Reality-Assisted Problem-Based Learning Model on the Critical Thinking Skills of 11th-Grade Students - Amilia Novella Dwita; Rosane Medriati; Fitri April Yanti (JagoMIPA: Jurnal Pendidikan Matematika dan IPA, 2026)
The purpose of this study is to characterize the impact and extent of the PBL model with AR assistance on the critical thinking abilities of eleventh-grade dynamics students. The low degree of critical thinking abilities is the study's backdrop and students’ difficulty in understanding complex physics concepts that require conceptual analysis. This study employed a quasi-experimental research design using a nonequivalent control group design with purposive sampling to select one experimental class and one control class. The experimental group received PBL assisted by AR, whereas the control group received PBL without AR assistance. Both groups completed a pretest before the learning intervention and a posttest after the intervention. An essay test based on Ennis’s critical thinking indicators measured students' critical thinking skills. The instrument showed high reliability, with a Cronbach’s alpha coefficient of 0.894. The study collected data through pretests and posttests and analyzed the data using the Mann–Whitney U test. The results showed a statistically significant difference between the two groups, with the experimental class obtaining an average posttest score of 53.38, higher than the control group’s 43.42. An effect size of 0.278 indicates an effect in the small-to-moderate range. These results imply that the combination of PBL and AR promotes the growth of critical thinking abilities via contextual problem-solving and concrete visualization of concepts. Thus, AR-assisted PBL effectively enhances students' critical thinking skills. Future research should evaluate the effectiveness of AR-assisted PBL across different physics topics, educational levels, and larger samples.